Nutritional intake of university employees'. Issue 2 (5th February 2018) - Lima, João Pedro Marques; Costa, Sofia A.; Rocha, Ada
Abstract : Purpose: Excessive high caloric and nutritional intake has been associated with weight gain which is linked to an increased prevalence of cardiovascular disease, type 2 diabetes and several types of cancers. The purpose of this paper is to characterize the nutritional intake pattern of the population in terms of energy, macro and micronutrients. Design/methodology/approach: There were assessed 513 workers of the University of Porto (UP) randomly selected. The Food Processor Plus was used to convert foods into nutrients and, to assess nutritional intake adequacy. Data were compared to Dietary Reference Intakes and with recommended ranges by the World Health Organization. Findings: The intake of most individuals was above recommendations for protein, carbohydrates and sodium. The average of energy intake observed in UP employees was lower than data available for Portuguese general population. The protein, carbohydrates, total fat and water intake, cholesterol, saturated, monounsaturated, polyunsaturated fatty acids and sodium intake were found to be significantly higher for men. Significant differences were found for vitamin D and calcium between age ranges; Carbohydrates, sugar, monounsaturated fatty acids, cholesterol, water and vitamin K was significantly different between teachers and non-teachers. Originality/value: According to nutritional intake analysis, food consumption of this population was unbalanced, attending to high protein, carbohydrates and sodium intake.